Perceptions of community care workers on their roles and responsibilities: Soshanguve, Pretoria - Mawadzwa, Tronny (My University, 2021)
Care workers play a pivotal role in the community affected by HIV/AIDS through regular home visits. The purpose of this research was to understand better the perceptions of care workers who provide services to HIV/AIDS home visits in the community of Soshanguve. The researcher used research strategy because the study was concerned with collecting data about the care workers’ perceptions and opinions about the services offered to HIV/AIDS-affected individuals and their families. The researcher selected a phenomenology research design for this research to help understand the perceptions and experiences of care workers, and it allowed for an in-depth analysis of the information from a single group of care workers. The researcher used semi-structured interview guides to ask questions in a focus group set up and on individuals as Key Informants’ Interviews (KIIs). A sample of 9 care workers took part in the study, broken down into one focus group with 7 participants and 2 KIIs were conducted as well. The findings from the study indicate that care workers have fragmented roles and responsibilities that are always changing. The working conditions are not safe for their health and safety. Care workers reported that they recognized by higher superiors and are forced to work under harsh weather conditions with tight targets to accomplish every month. Findings indicate that care workers require adequate training and psychosocial support to help them cope with emotional stress. Lastly, the remuneration of care workers has to be revised as data collected showed that the stipend they receive does not sustain their basic living conditions. Care workers have a passion for assisting the government meet their sustainable development goals on HIV/AIDS. For care workers to effectively perform at work, roles and responsibilities have to be fixed, their working conditions improved, provide training and psychosocial support and revise their stipend
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, of the requirements for the degree of Master of Management (in the field of Monitoring and Evaluation), 2021
Keywords: UCTD; COMMUNITY CARE WORKERS; HIV/AIDS; Soshanguve; SDG-3: Good health and well-being